Tailored Double Emulsions Made Simple (Adv. Mater. 5/2022). Issue 5 (3rd February 2022) - Wang, Junwei; Hahn, Simon; Amstad, Esther; Vogel, Nicolas
Abstract : Single‐Core Double Emulsions The fabrication of single‐core double emulsions typically requires sophisticated microfluidic devices and meticulous operation protocols. In article number 2107338, Nicolas Vogel and co‐workers develop a convenient method to produce such tailored double emulsions with defined droplet structure using only vortex mixing. This fast, low‐cost and high‐yield method improves the accessibility of droplet‐based materials.